PEMBELAJARAN AKIDAH MELALUI KAJIAN INTERAKTIF BERBASIS MULTIMEDIA - Wibowo, Irham (Institut Agama Islam Negeri Ternate, 2024)
Not a few Muslims and Muslim women still go to shamans to ask for help and it is a sad thing that Islam with its noble and rational teachings has negated things that are irrational. Therefore, in collaboration with Radio EMC 97.8 FMPuspita Radja Yogyakarta, the ‘Mutiara Ramadhan 1445 Hijriyah’ activity was held. The big theme raised is related to the faith chapter, while the sub-theme of the discussion outlined is related to magic and shamanism. Through radio media and other supporting multimedia devices such as YouTube live streaming, it is hoped that the target segmentation, apart from parents, is the younger generation. The methods used are lectures and interactive dialogue (question and answer). The audience in this activity found it very useful because it helped them increase their understanding of religion, especially the pure Islamic faith.Keywords: Islamic creed; Multimedia Studies; Da'wah.